2011
DOI: 10.1128/aac.00294-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Genetic Barriers and Pathways towards Resistance of Selective Inhibitors of Hepatitis C Virus Replication

Abstract: Hepatitis C virus (HCV) inhibitors include direct-acting antivirals (DAAs) such as NS3 serine protease inhibitors, nucleoside and nonnucleoside polymerase inhibitors, and host-targeting antivirals (HTAs) such as cyclophilin inhibitors that have been developed in recent years. Drug-resistant HCV variants have been reported both in vitro and in the clinical setting for most classes of drugs. We report a comparative study in which the genetic barrier to drug resistance of a representative selection of these inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 70 publications
4
47
0
Order By: Relevance
“…Our attempts to select for resistance to 2CMC in Norwalk virus replicon-carrying cells were unsuccessful (data not shown), which is in line with our failure to select 2CMC-resistant MNV (17). Also against HCV, the barrier to resistance of this nucleoside analogue is high (23).…”
Section: Discussionsupporting
confidence: 53%
“…Our attempts to select for resistance to 2CMC in Norwalk virus replicon-carrying cells were unsuccessful (data not shown), which is in line with our failure to select 2CMC-resistant MNV (17). Also against HCV, the barrier to resistance of this nucleoside analogue is high (23).…”
Section: Discussionsupporting
confidence: 53%
“…The loss of activity of benzothiadiazines, such as setrobuvir, against G2a and G3a viruses is consistent with previous reports on chimeric replicons (29,30,32) and recombinant G2a and G3a RdRps (27,28). Resistance to benzothiadiazines in G2a and G3a viruses appears to be due to the glycine residue at position 556 (55,56) of the RdRp, an amino acid substitution which was detected in benzothiadiazine-resistant G1 replicons (60) and in G1 HCV-infected patients after treatment (61). Surprisingly, mutating G556 in the G3a RdRp to a serine, the residue naturally occurring in the G1b enzyme, did not confer susceptibility to benzothiadiazines, at least in recombinant RdRp studies (27).…”
Section: Discussionsupporting
confidence: 78%
“…Surprisingly, the C445C/F mutation was also observed following treatment with JT-16, a site I non-nucleoside NS5B inhibitor whose binding pocket does not involve the 445 residue. Clonal sequencing of RNA from the replicon cells revealed that the C445F mutation pre-exists at a frequency of 3.4% (Delang et al, 2011). Moreover, replicons carrying this mutation were markedly more fit when compared to wild-type replicons (Delang et al, 2011).…”
Section: Discussionmentioning
confidence: 98%